Recurrent takotsubo syndrome in a patient with myotonic dystrophy 1. (December 2014) - Finsterer, Josef; Stöllberger, Claudia; Demirtas, Dita; Gencik, Martin; Ohnutek, Irene; Hornykewycz, Anette
Abstract Objectives: Stress-induced cardiomyopathy (takotsubo-syndrome, TTS) and its recurrence have not been described in myotonic dystrophy-1. Case report: The patient was a 47-year-old female who was suspected to suffer from myotonic dystrophy-1 at 20 years of age, upon the typical clinical presentation and the electrophysiological findings. During weaning from general anesthesia for resectioning of a pelvic tumour she developed ventricular fibrillation, but was successfully resuscitated. During coronary angiography two days later she experienced recurrent QT-prolongation, torsades de pointes, and ventricular fibrillation, but was successfully resuscitated again each time. Echocardiography and electrocardiography were indicative of TTS, which was confirmed by normal findings on echocardiography and electrocardiography two months later. Ten months after the first TTS she developed dyspnea, leg edema, and anginal chest pain. Recurrence of TTS was diagnosed upon a typical electrocardiography and echocardiography findings. Shortly after onset of the second TTS, she unexpectedly died from sepsis. Conclusions: TTS may also occur in patients with myotonic dystrophy-1 induced by stress from surgery, respiratory insufficiency, or infection. In patients with myotonic dystrophy-1, takotsubo-syndrome may recur and may represent a previously unreported feature of cardiac involvement in myotonic dystrophy-1.